1960
DOI: 10.1136/jcp.13.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic and Antifibrinolytic Activity in Pregnancy

Abstract: Fibrinolytic activity and serum antifibrinolysin were estimated in normal pregnant women, during and after labour.The decreased fibrinolytic activity found during labour returned to non-pregnant levels within 24 hours of delivery. During the same period, the serum antifibrinolysin was rapidly diminished.It is suggested that the post-partum increase in fibrinolytic activity to non-pregnant levels is due to alterations in the fibrinolytic system itself, as well as to changes in circulating antifibrinolysin.In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The fall and recovery of fibrinogen and factors V and VIII thus appear to be independent of changes in blood volume and to reflect changes in concentration during the immediate puerperium. The fibrinolytic activity, as indicated by the euglobulin lysis time, decreases in late pregnancy, increascs sharply in the first 24 hr postpartum, then returns to pre-existing lcvcls (Guest, 1954;Naidoo et al, 1960;Shaper et al, 1966). We have corroborated thcsc findings but our additional data indicate that twin births do not show this phenomenon, decreased fibrinolytic activity being noted throughout the 24 hr period.…”
Section: I73supporting
confidence: 80%
“…The fall and recovery of fibrinogen and factors V and VIII thus appear to be independent of changes in blood volume and to reflect changes in concentration during the immediate puerperium. The fibrinolytic activity, as indicated by the euglobulin lysis time, decreases in late pregnancy, increascs sharply in the first 24 hr postpartum, then returns to pre-existing lcvcls (Guest, 1954;Naidoo et al, 1960;Shaper et al, 1966). We have corroborated thcsc findings but our additional data indicate that twin births do not show this phenomenon, decreased fibrinolytic activity being noted throughout the 24 hr period.…”
Section: I73supporting
confidence: 80%
“…Opinions differ also about the plasminogen level during pregnancy. Thus Shaper et al (27) and Brakman (4) found no difference between the plasminogen levels in pregnant and nonpregnant women, while Naidoo et al (19) found them to be low during pregnancy. Most authors have, however, reported high values of plasminogen during pregnancy (15, 18, 20, 22).…”
Section: Discussionmentioning
confidence: 97%
“…The spontaneous fibrinolytic activity in the blood is substantially reduced during pregnancy (2, 3, 4, 13, 20,27). The mechanism of this relatively low fibrinolytic activity in pregnancy is, however, still obscure, some workers ascribing it to an increased content of inhibitors in the blood (2, 13, 14, 18,19,22); and others, to a decreased production or release of plasminogen activators from the vessel walls (3, 4,20,28). This lack of unanimity is accentuated by the fact that some authors did not find any increase in inhibitors (1, 5 , 23).…”
mentioning
confidence: 99%